Airborne observations of peroxy radicals during the EMeRGe campaign in Europe - George, Midhun; Andrés Hernández, Maria Dolores; Nenakhov, Vladyslav; Liu, Yangzhuoran; Burrows, John P.; Bohn, Birger; Förster, Eric; Obersteiner, Florian; Zahn, Andreas; Harlaß, Theresa; Ziereis, Helmut; Schlager, Hans; et al. (Atmospheric chemistry and physics, 2023)
In this study, airborne measurements of the sum of hydroperoxyl (HO2) and organic peroxy (RO2) radicals that react with nitrogen monoxide (NO) to produce nitrogen dioxide (NO2), coupled with actinometry and other key trace gases measurements, have been used to test the current understanding of the fast photochemistry in the outflow of major population centres. The measurements were made during the airborne campaign of the EMeRGe (Effect of Megacities on the transport and transformation of pollutants on the Regional to Global scales) project in Europe on board the High Altitude and Long Range Research Aircraft (HALO). The measurements of RO2∗ on HALO were made using the in situ instrument Peroxy Radical Chemical Enhancement and Absorption Spectrometer (PeRCEAS). RO2∗ is to a good approximation the sum of peroxy radicals reacting with NO to produce NO2. RO2∗ mixing ratios up to 120 pptv were observed in air masses of different origins and composition under different local actinometric conditions during seven HALO research flights in July 2017 over Europe. - - Radical production rates were estimated using knowledge of the photolysis frequencies and the RO2∗ precursor concentrations measured on board, as well as the relevant rate coefficients. Generally, high RO2∗ concentrations were measured in air masses with high production rates. In the air masses investigated, RO2∗ is primarily produced by the reaction of O1D with water vapour and the photolysis of nitrous acid (HONO) and of the oxygenated volatile organic compounds (OVOCs, e.g. formaldehyde (HCHO) and glyoxal (CHOCHO)). Due to their short lifetime in most environments, the RO2∗ concentrations are expected to be in a photostationary steady state (PSS), i.e. a balance between production and loss rates is assumed. The RO2∗ production and loss rates and the suitability of PSS assumptions to estimate the RO2∗ mixing ratios and variability during the airborne observations are discussed. The PSS assumption for RO2∗ is considered robust enough to calculate RO2∗ mixing ratios for most conditions encountered in the air masses measured. The similarities and discrepancies between measured and PSS calculated RO2∗ mixing ratios are discussed. The dominant terminating processes for RO2∗ in the pollution plumes measured up to 2000 m are the formation of nitrous acid, nitric acid, and organic nitrates. Above 2000 m, HO2-HO2 and HO2-RO2 reactions dominate the RO2∗ removal. RO2∗ calculations by the PSS analytical expression inside the pollution plumes probed often underestimated the measurements. The underestimation is attributed to the limitations of the PSS equation used for the analysis. In particular, this expression does not account for the yields of RO2∗ from the oxidation and photolysis of volatile organic compounds, VOCs, and OVOCs other than those measured during the EMeRGe research flights in Europe. In air masses with NO mixing ratios ≤50 pptv and low VOC/NO ratios, the RO2∗ measured is overestimated by the analytical expression. This may be caused by the formation of H2O and O2 from OH and HO2, being about 4 times faster than the rate of the OH oxidation reaction of the dominant OVOCs considered.
Veröffentlicht: 14. Juli 2023
Gesehen am 23.08.2023